Digital Technology Adaptation Challenges to Enhance Growth and Security of Corporate Online Businesses - Yatna, Chicilia Nova; Banjuradja, Sylvia Yuanita; Sutrisno, Sutrisno; Ritawaty, Noor (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study examines the challenges of digital technology adaptation faced by corporate online businesses, focusing on the interplay between growth opportunities and security requirements. The study aims to comprehensively understand technical, security, and organizational barriers while offering actionable strategies to overcome these obstacles. Research Design and Methodology: The study employs a qualitative systematic literature review (SLR) methodology to synthesize findings from recent scholarly contributions. The review integrates theoretical frameworks such as the Technology Acceptance Model (TAM) and organizational innovation theories to contextualize digital adaptation's challenges and potential solutions. Findings and Discussion: The findings reveal that successful digital adaptation is hindered by technical complexities such as integrating AI and IoT, cybersecurity threats, including ransomware and phishing, and organizational resistance due to limited digital literacy and employee readiness. A holistic approach that combines robust security measures, employee training programs, and cultural transformation is critical for addressing these challenges. The discussion highlights the importance of aligning organizational strategies with advanced technologies to foster operational resilience and market competitiveness. Implications: This study provides valuable insights for business leaders and policymakers. Practically, it emphasizes the need for proactive security integration, workforce upskilling, and leveraging AI for enhanced operational efficiency. From a managerial perspective, fostering innovation-supportive cultures and aligning technological strategies with organizational goals is critical. Policymakers are encouraged to create regulatory frameworks that balance technological innovation with robust security measures to promote sustainable business growth.